Theory of Applied Robotics Kinematics, Dynamics, and Control (2nd Edition) - Jazar, Reza N.; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
Theory of Applied Robotics: Kinematics, Dynamics, and Control (2nd Edition) explains robotics concepts in detail, concentrating on their practical use. Related theorems and formal proofs are provided, as are real-life applications. The second edition includes updated and expanded exercise sets and problems. New coverage includes: components and mechanisms of a robotic system with actuators, sensors and controllers, along with updated and expanded material on kinematics. New coverage is also provided in sensing and control including position sensors, speed sensors and acceleration sensors. Students, researchers, and practicing engineers alike will appreciate this user-friendly presentation of a wealth of robotics topics, most notably orientation, velocity, and forward kinematics.
Kinematics -- Rotation Kinematics -- Orientation Kinematics -- Motion Kinematics -- Forward Kinematics -- Inverse Kinematics -- Angular Velocity -- Velocity Kinematics -- Numerical Methods in Kinematics -- Dynamics -- Acceleration Kinematics -- Motion Dynamics -- Robot Dynamics -- Control -- Path Planning -- ? Time Optimal Control -- Control Techniques.
Keywords: Engineering; Systems theory; Vibration; Control engineering systems; Engineering; Vibration, Dynamical Systems, Control; Control , Robotics, Mechatronics; Systems Theory, Control